The Role of Environmental Literacy in Students’ Environmental Problem-Solving Ability at Adiwiyata School: A Study at SMA Negeri 8 Semarang - Ayu Andini, Adzani; Sriyanto, Sriyanto (LPPM Universitas Jambi, 2026)
Environmental literacy and environmental problem-solving ability are two essential competencies students need in order to address Indonesia’s growing environmental problems. This study aims to analyze the level of environmental literacy, the level of environmental problem-solving ability, and the relationship between the two among students of SMA Negeri 8 Semarang, a provincial Adiwiyata school operating under both Kurikulum Merdeka and the 2013 Curriculum. A quantitative correlational approach was used with a sample of 91 students selected through proportionate stratified random sampling from a population of 1,074 students. Data were collected through a multiple-choice test, a questionnaire, and observation, then analyzed using descriptive statistics and Pearson product-moment correlation after the normality and linearity assumptions were satisfied. The findings indicate moderate levels of both environmental literacy and problem-solving capacity among students. Correlation analysis revealed a statistically significant, moderately strong positive relationship, proving that literacy meaningfully drives variations in problem-solving skills. Strengthening environmental literacy can thus enhance students' problem-solving capabilities, complemented by hands-on experiences such as project-based learning. This study contributes to environmental education literature by demonstrating how green school frameworks foster functional competencies across concurrent curricula. Practically, it recommends consistently integrating project-based environmental learning across all grade levels to ensure cohesive skill development.